Is Progressive Ideology on the Test? Education and Intelligence in the Development of Nontraditional Attitudes - Isen, Joshua D.; Ludeke, Steven G.; Bainbridge, Timothy F.; McGue, Matt K.; Iacono, William G. (Personality & social psychology bulletin, 2024)
Enhanced educational attainment and intelligence are consistent correlates of socially liberal, nontraditional attitudes. However, it is unclear how such associations unfold developmentally. Here, we propose an interaction effect between college exposure and intelligence on the development of nontraditional attitudes. Our rationale builds from the fact that a desired learning outcome of college education is to challenge traditional dogma and encourage diverse perspectives. Those with higher intellectual ability should be particularly adept at understanding the intended lesson and to show attendant increases in nontraditional attitudes. Data on social attitudes were obtained in a large community sample of youth at age 17 and remeasured at two points in early adulthood ( N = 2,769). Intelligence was linked with growth in nontraditional attitudes among those with higher educational attainment; no such association was observed among individuals who never attended college. Environments that encourage critical inquiry may thus steer brighter individuals toward the adoption of progressive worldviews.